Strength and conditioning for judo - Burns, A.; Callan, M. (The Crowood Press Ltd., 2017)
Judo is a dynamic Olympic sport that requires a wide range of physical attributes and skills. It is the second largest participation sport in the world after football, and estimates suggest there are 20 million judoka (practitioners of judo) just in Europe. However strength and conditioning are prerequisites for an aspiring judoka, and this book is essential reading for judo coaches, strength and conditioning professionals, and judoka alike. Topics covered include: needs analysis of judo; building strength and delivering power; co-ordination, speed and agility; the importance of nutrition; and finally, injury prevention and maximizing recovery. Essential reading for judo practitioners, judo coaches and strength & conditioning professionals and extensively illustrated with 139 colour photographs and diagrams.